Five Years and Count(er)ing: Memoir after Memoir. Issue 1 (April 2020) - Bugeja, Norbert
Abstract : In this retrospective piece, the Guest Editor of the first number of CounterText (a special issue titled Postcolonial Springs ) looks back at the past five years from various scholarly and personal perspectives. He places particular focus on an event that took place mid-way between the 2011 uprisings across a number of Arab countries and the moment of writing: the March 2015 terror attack on the Bardo National Museum in Tunis, which killed twenty-two people and had a profound effect on Tunisian popular consciousness and that of the post-2011 Arab nations. In this context, the author argues for a renewed perspective on memoir as at once a memorial practice and a political gesture in writing, one that exceeds concerns of genre and form to encompass an ongoing project of political re-cognition following events that continue to remap the agenda for the region. The piece makes a brief final pitch for Europe's need to re-cognise, within those modes of 'articulacy-in-difficulty' active on its southern borders, specific answers to its own present quandaries.